Effect of Bisphenol A on Expression of Estrogen-, Retinoid- and Thyroid Hormone-Related Genes in the Green Catfish (Mystus nemurus) - Leelawatwattana, Ladda; Sokul, Peasala; Khwanmunee, Jiraporn (Journal of Fisheries and Environment, 2024)
The impact of bisphenol A (BPA), a chemical known for its endocrine-disrupting ability, has been investigated in various fish species. This study aimed to examine the effect of BPA on the expression of genes associated with estrogen, retinoid, and thyroid hormones in green catfish (Mystus nemurus). The isolated cDNA fragments, which were 414, 319, 445, and 366 base pairs in length, exhibited significant similarity to brain cytochrome P450 aromatase (cyp19b), transglutaminase-2 (tgase-2), deiodinase type III (dio3), and thyroid hormone receptor alpha (trα), respectively. When translated into amino acids, these cDNA fragments corresponded to approximately 30%, 15%, 55%, and 30% of the full-length length P450AromB, TGase-2, Dio3, and TRα proteins in different fish species, respectively. At 15 days post-hatching, green catfish were exposed to BPA at concentrations of 0.01, 10, 100, and 1,000 nM for three days. The expression of cyp19 decreased compared to the control group when fish were exposed to BPA at 0.01 and 10 nM. The mRNA expression levels of tgase and tr also decreased across all treatment groups compared to the control group. However, no significant changes were observed in the expression of dio across the investigated doses. The study’s findings indicate that exposure to BPA at ecologically relevant concentrations leads to changes in gene expression in green catfish.